Microplastic pollution and ecological risks in the wet season: Potential effects on bacterial communities and nitrogen cycling in a coastal watershed of Southeast China - Yaling Huang; Suofang Zhong; Wantao Lin; Shoufeng Zhang; Hua Jiang; Xuan Wang; Jingli Mu (Marine Pollution Bulletin, 2026)

Ruddlesden–Popper La2CoO4 with surface hydroxyl engineering for efficient catalytic hydrolysis of organophosphate esters and in situ phosphate immobilization - Jinwei Wang; Yaling Dai; Ruihan Wang; Yi Liu; Xiangjun Yang; Fengzhi Jiang; Xia Luo; Siping Ji; Zhiguo Lin (Environmental Research, 2026)

Resilience and reconfiguration: A CPD-STERGM analysis of structural breaks in the BRI LIB trade network - Xingxuan Zhuo; Yaling Cai; Liuqing Lin (Journal of Cleaner Production, 2026)

Role of Glass Transition Mismatch in Rice Quality Deterioration During Hot-Air Drying - Wenting Xu; Yafang Shao; Xiaoyan Lin; Yaling Chen; Dawei Zhu (Journal of Cereal Science, 2026)

Single-nucleus RNA sequencing reveals cellular heterogeneity in Holstein dairy cows with different milk production volumes - Chuanchuan Wang; Yafei Chen; Xiaofang Feng; Chao Yan; Yun Ma; Xiaohua Tian; Xiaoyun Ji; Lin Xue; Hua Wang; Juan Zhang; Yaling Gu (Food Bioscience, 2026)

Sulfur-doped cyanobacterial biochar-supported Co-Fe spinel oxide with enriched oxygen vacancies: overcoming redox and electron transfer limitations in Fenton-like sulfadiazine removal - Chen He; Yaling Dai; Jinwei Wang; Zhiguo Lin; Linxin Zhao; Fengzhi Jiang; Xia Luo; Siping Ji; Xiangjun Yang (Bioresource Technology, 2026)

Contrasting Effects of Nitrogen Input on Soil Carbon Pools in Arid and Humid Climates - Shibing Jia; Cuihuan Li; Zhenfeng Xu; Bo Tan; Xinglei Cui; Guopeng Liang; Han Li; Li Zhang; Lin Xu; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Global Change Biology, 2026)
Nitrogen (N) input affects soil organic carbon (SOC) dynamics and storage by specifically influencing the light (LFOC) and heavy fractions of organic C (HFOC). While the effects of N input on SOC pools are known, its specific influence in arid and humid regions remains unresolved, although it is critically important to predict carbon–climate feedback and SOC accumulation. We conducted a meta‐analysis of 881 paired observations from 60 studies to quantify the climate‐specific responses of SOC, LFOC, and HFOC contents to N input, thereby revealing distinct effects in arid versus humid regions. N input increased the LFOC content by 25% in arid regions, whereas the HFOC and SOC contents remained unchanged. This LFOC accumulation may reflect increased plant C inputs, suppressed microbial decomposition, and strong physical protection compared with soil without N input. Conversely, in humid regions, N input increased the HFOC and SOC contents by 10%. These increases were associated with the following four mechanisms: (1) increases in plant and microbial necromass production after N input, (2) microbially‐mediated formation of the HFOC from the LFOC, (3) accelerated lignin‐derived C accumulation due to suppressed saprotrophic fungal decomposition, and (4) raised physico–chemical stabilization by various biotic and abiotic mechanisms. Specifically, increases in LFOC content in arid regions occurred under medium to high N input rates (≥ 50 kg N ha −1 year −1 ), whereas increases in HFOC and SOC contents in humid regions occurred only under medium N input (50–100 kg N ha‐1 year −1 ). These increases occurred primarily after periods of N input longer than 5 years and mainly in topsoil (

Nutritional Programming in Yellow Catfish: Dietary Phaffia rhodozyma Effects on Growth Performance, Antioxidant Capacity, and Intestinal Health - Shengjie Lin; Yaling Wang; Tengyang Lu; Muhammad Jawad; Haijing Xu; Qingwen Zhou; Aimin Wang; Mingyou Li (Fishes, 2026)
The sustainable production of yellow catfish (Pelteobagrus fulvidraco) fry is critical for aquaculture, yet early developmental stages face high mortality and nutritional challenges. This study evaluated the effects of dietary supplementation with broken-cell wall P. rhodozyma on growth performance, organ development, enzyme activities, and gut microbiota composition in yellow catfish fry. Dietary supplementation with broken-cell wall P. rhodozyma significantly improved fry performance, increasing survival from 12% to 52%, promoting growth, enhancing intestinal and liver development, improving digestive enzyme activities, and modulating antioxidant-related physiological responses. It also elevated beneficial Muribaculum and reduced Streptococcus in the gut, promoting microbiota stability. These results demonstrate that P. rhodozyma supplementation not only improves early growth, organ maturation, stress resistance, and intestinal health but also effectively enhances overall fry health and development, thus supporting its use as a functional feed additive in aquaculture.

A robust decision-support framework for urban green space planning: Integrating biophysical supply and social vulnerability for thermal resilience in a high-density city - He Huang; Yan Chen; Weichen Guo; Lijingjing Lu; Jinwen Jiang; Hongrui Lin; Xiao Zhang; Sishi Chen; Yaling Gao (Urban Climate, 2026)

Glutamate-amended chicken manure composting reduces nitrous oxide emissions through promoting ammonium assimilation and complete denitrification - Yanan Luo; Yinfeng Yang; Xiaolin Lu; Wenyu Huang; Yaling Peng; Shangyu Lin; Qunliang Li (Journal of Environmental Chemical Engineering, 2026)

Analysis of the characteristics of rumen microorganisms and their metabolites and plasma metabolites in crossbred beef cattle at different stages - Xiaohua Tian; Yuan Feng; Chuanchuan Wang; Wei Zhao; Lin Xue; Ling Zhu; Xiaoyun Ji; Hua Wang; Yaling Gu; Qiufei Jiang; Juan Zhang (Veterinary Research Communications, 2026)

Stand age drives divergent microbial metabolic limitations and ecosystem multifunctionality between rhizosphere and bulk soils in subtropical Cryptomeria japonica plantations - Shanshan Huang; Yi Jian; Jing Li; Dengjie Zhou; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Lixia Wang; et al. (Soil Ecology Letters, 2026)

Integrating multi-omics to characterize the dynamics of rumen microorganisms and metabolites in Angus cattle at different growth stages - Lin Xue; Wei Zhao; Chuanchuan Wang; Yun Ma; Jinli Tian; Lijuan Yang; Lina Ma; Qiufei Jiang; Yafei Chen; Xiaohua Tian; Xiaoyun Ji; Juan Zhang; et al. (Research in Veterinary Science, 2026)

Screening, risk assessment, and rapid detection of mycotoxins in edible herbs based on UPLC-MS/MS and FT-NIR - Kangnan Liu; Ling Fang; Yaling An; Zijun Tang; Wenjie Zhao; Chunqian Song; Lin Feng; Xiaokang Liu; Zhenwei Li; Daidi Zhang; De-an Guo (Food Research International, 2026)

Patterns and drivers of plant- and microbial-derived carbon in a cedar plantation chronosequence of subtropical China - Yuehan Wang; Yu Li; Chengming You; Hongwei Xu; Han Li; Lin Xu; Li Zhang; Lixia Wang; Sining Liu; Bo Tan; Yaling Yuan; Jiao Li; et al. (Plant and Soil, 2026)

Based on sensory evaluation, E-nose, and GC-IMS analysis of volatile component differences in various kinds of sheep fats - Yaping Wang; Xiaolei Tang; Xitong Yuan; Hanying Xu; Yuxi Liu; Yaling Yang; Zhihui Lin; Siming Wang; Bin Qi; Li Liu (Natural Product Research, 2026)

Enhancing urban bird corridor identification by integrating three-dimensional factors: A validation with citizen science data - Yaling Huang; Ziru Chen; Yankai Huang; Tongyan Li; Chengyu Ran; Ying Lin; Yinghong Ding; Deng Pan; Yuxiang Lan; Jiali Jin; Zhipeng Zhu; Weicong Fu (Urban Forestry & Urban Greening, 2026)

Impact of precipitation pH of hydrated ferric oxide on calcium-enhanced phosphate adsorption from water - Yaling Xie; Jianwei Lin; Yanhui Zhan (Chemical Engineering Journal, 2026)

Monitoring surface water in floodplains by satellites: Progress, challenges, and perspectives - Yaling Lin; Chunqiao Song (Journal of Hydrology, 2026)

Integrated Aerobic Exercise and Multisensory Environment Training for Age-related Cognitive Decline via Hippocampal-prefrontal Neural Circuit Modulation - Huawei Lin; Yuxi Qiu; Zhongyi Hu; Liming Chen; Yaling Dai; Tao Jiang; Rui Li; Sinuo Wang; Yajun Cao; Jianhong Li; Huanhuan Liu; Yuwei Ye; et al. (Molecular Neurobiology, 2026)

Construction of high-strength multifunctional flexible sensors based on hydrophobic aggregation phase separation induced by differences in aggregation rate - Jianjun Chen; Xinyi Xiong; Ning Yu; Anqiang Zhang; Yaling Lin (Chemical Engineering Journal, 2025)

Regulating the morphological structure of cellulose acetate ultrafiltration membrane by adjusting the ratio of N, N-dimethylacetamide: N-methyl pyrrolidone in co-solvent to enhance separation and anti-fouling performance - Minfu Mo; Yaling Lin; Danni Lin; Xiaojuan Ma; Yubin Hong; Lihui Chen; Dong Wang; Liulian Huang (Desalination, 2025)

Estimating the vegetable yield and carbon reduction benefits of urban agriculture in Fuzhou based on planting intensity - Qunyue Liu; Zhiqian Lin; Taoyu Chen; Ni Zhang; Zubin Ye; Yourui Guo; Yaling Gao; Yuanping Shen; Weicong Fu; Yuanjing Wu (Sustainable Cities and Society, 2025)

Degradation of tetracycline dominated by non–radical pathway: Oxygen vacancies in CuFe2O4 as key triggering factors for enhanced peroxymonosulfate activation - Chen He; Jinwei Wang; Jinyang Liu; Yaling Dai; Qiqi Liu; Zhicun Zhou; Boxian Ren; Zhiguo Lin; Xiangjun Yang (Journal of Environmental Chemical Engineering, 2025)

Hedgehog-nanovesicles redox probe based “explosive” signal amplification biosensing platform for Alzheimer's disease early diagnosis - Yuanzhe Li; Wenchen Gu; Yaling Li; Zheng Zhao; Ting Liu; Peifeng Ke; Haibiao Lin; Qiqin Wang; Xianzhang Huang; Qiaoxuan Zhang (Chemical Engineering Journal, 2025)

Characterizing the capability of public DEMs for mapping global floodplain bathymetry - Yaling Lin; Chenyu Fan; Kai Liu; Lingyang Liu; Xinyuan Deng; Pengju Xu; Pengfei Zhan; Xuefei Fu; Chunqiao Song (Journal of Hydrology, 2025)

Exploring the role of the rhizosphere in soil carbon cycling: impacts on pools and components of SOC along a chronosequence of Cryptomeria japonica plantations in subtropical China - Dengjie Zhou; Yaling Yuan; Jing Li; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Lin Xu; Li Zhang; Hongwei Xu; Lixia Wang; Sining Liu; et al. (Plant and Soil, 2025)

Multifunctional motion sensor for health monitoring and treating movement disorders: Construction of tough and elastic multiphase hydrogel based on nanoparticle-micelle synergistic interfacial crosslinking strategy - Jianjun Chen; Ning Yu; Anqiang Zhang; Yaling Lin (Chemical Engineering Journal, 2025)

Freeze-thaw characteristics of seasonal frozen soil in Asian mid-latitude deserts: A case study of typical deserts in northern China - Tianbo Xia; Ping Zhang; Yaling Hu; Juanli Ma; Juntian Lin; Yuan Liu; Lei Jin (CATENA, 2025)

Soil nutrients determine multidimensional absorptive root traits of Cryptomeria japonica var. sinensis plantations along a chronosequence in subtropical forest - Chunran Liu; Lihua Wang; Jing Li; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Lin Xu; Hongwei Xu; Li Zhang; Lixia Wang; et al. (Journal of Environmental Management, 2025)

Sediments in Yangzonghai Lake after engineering treatment with ferric salt flocculation for arsenic mitigation: source or sink?? - Boxian Ren; Jinwei Wang; Yaling Dai; Chen He; Shixiong Wang; Xiangjun Yang; Zhiguo Lin; Conghai Zhang (Journal of Soils and Sediments, 2025)

Genome-wide association analysis reveals genetic loci and candidate genes for white diarrhea in Jingyuan chickens - Lijuan Yang; Siyu Chen; Wei Zhao; Guojun Zhang; Hu Zhang; Tong Zhang; Lin Xue; Jinli Tian; Yaling Gu; Lanlan Li; Hu Wang; Juan Zhang (Research in Veterinary Science, 2025)

Potential of submerged macrophytes restoration for reducing CH4 and CO2 emissions in a typical urban lake - Yifan Yin; Zhen Ci; Mengyi Qin; Hanqi Lin; Yiquan Zhang; Fan Xun; Aiyu Xie; Peng Xing; Xinfang Chen; Yaling Su; Muhua Feng (Journal of Environmental Management, 2025)

Climate outweighs fertiliser effects on soil phoD-harbouring communities in agroecosystems - Lin Xu; Yongping Kou; Qian Mao; Xiangzhen Li; Chaonan Li; Bo Tu; Jiabao Li; Lihua Tu; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Soil Biology and Biochemistry, 2025)

Mapping soil cadmium content using multi-spectral satellite images and multiple-residual-stacking model: Incorporating information from homologous pollution and spectrally active materials - Chao Tan; Haijun Luan; Qiuhua He; Yaling Zheng; Zhenhong Lin; Lanhui Wang (Journal of Hazardous Materials, 2025)

A comparative study of the composition of microorganisms and metabolites in different β-casein genetic types of dairy cows based on metagenomics and non-targeted metabolomics - Chuanchuan Wang; Jinyan Zhao; Wei Zhao; Lin Xue; Yafei Chen; Jia Tian; Hua Wang; Xiaoyun Ji; Xiaohua Tian; Juan Zhang; Yaling Gu (Food Research International, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Integrating lipidomics and metabolomics to reveal biomarkers of fat deposition in chicken meat - Wei Zhao; Jiahuan Hu; Lanlan Li; Lin Xue; Jinli Tian; Tong Zhang; Lijuan Yang; Yaling Gu; Juan Zhang (Food Chemistry, 2025)

Impact of urban landscape patterns on butterfly diversity in Fuzhou City parks - Ying Lin; Shanjun Huang; Wenqiang Fang; Yaling Huang; Chenfei Gao; Yankai Huang; Ruoxian Zheng; Weicong Fu (Science of The Total Environment, 2024)

Optimization study on circadian tunability and Rec. 2020 of RGB-LED-based displays considering the users with different ages - Qinzhen Lin; Ruoping Lian; Haoyang Liu; Wenhui Li; Junying Li; Yating Feng; Yi Lin; Suyao Liu; Weijie Liu; Kaiyu Yang; Yinxiao Yang; Yaling Chai; et al. (Energy and Buildings, 2024)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

Green energy meets urban agriculture: Unveiling the carbon reduction potential of Rooftop Agrivoltaics - Qunyue Liu; Taoyu Chen; Ni Zhang; Zubin Ye; Kunneng Jiang; Zhiqian Lin; Yaling Gao; Yourui Guo; Aifang Weng (Journal of Cleaner Production, 2024)

A poly (L-glutamic acid)-based porous scaffold with controllable and sequential release of kartogenin for enhanced cartilage regeneration - Xi Yu; Feng Lin; Yaling Zhuang; Shifeng Yan; Kunxi Zhang; Wenguo Cui; Jingbo Yin (Chemical Engineering Journal, 2024)

A dual-action Rhein-peptide hydrogel synergistically inhibits inflammation and matrix degradation for therapeutic mitigation of abdominal aortic aneurysm - Mingliang Wang; Yaling Li; Yizhou Bai; Zien Lin; Shenghui Bi; Yunxiang Long; Yanbin Cai; Xiaowu Wang (Chemical Engineering Journal, 2024)

The robustness waterproof ionogel based on the phase separation to form soft hard heterostructures and the interaction of cation-π realizes underwater adhesion and sensing - Ning Yu; Peiqi Liu; Yaling Lin; Anqiang Zhang (Chemical Engineering Journal, 2024)

Divergent rainfall infiltration patterns on the Chinese Loess Plateau between growing and non-growing seasons after long-term revegetation - Ruoxuan Li; Bihang Fan; Zhao Jin; Mingkui Hao; Hu Liu; Yaling Zhang; Yanjia Jiang; Hongyu Yao; Ke Lin; Li Guo (Journal of Hydrology, 2024)

Utilizing spontaneous plants for sustainable development in residential green spaces: Insights from environmental drivers and niche analysis in Fuzhou City, China - Chengyu Ran; Junyi Pan; Yuxin Lin; Tongyan Li; Yaling Huang; Jingkai Huang; Shiyuan Fan; Wenqiang Fang; Shuang Zhao; Yuxiang Liu; Jiali Jin; Weicong Fu (Journal of Environmental Management, 2024)

Emerging global reservoirs in the new millennium: Abundance, hotspots, and total water storage - Chenyu Fan; Chunqiao Song; Jida Wang; Yongwei Sheng; Yaling Lin; Chunyu Yuan; Md Safat Sikder; Jean-François Crétaux; Kai Liu; Tan Chen; Fanxuan Zeng; Linghong Ke (Science Bulletin, 2024)

Intelligent chemical profiling of 73 edible flowers by liquid chromatography-high resolution mass spectrometry combined with HRMS database and their authentication based on large-scale fingerprints - Ziqing Li; Jianqing Zhang; Lin Yang; Xiaolan Li; Qian Meng; Yun Li; Shuai Yao; Wenlong Wei; Qirui Bi; Hua Qu; Yaling An; De-an Guo (Food Chemistry, 2024)

Orbital global change drove fluvial aggradation and incision in Tibetan upper Mekong river: Chronological perspectives - Yinjun Zhou; Junfeng Han; Qinjing Shen; Yantian Xu; Yaling Tao; Penghui Lin; Yuansen Lai; Yixuan Wang; Zhongping Lai (Quaternary Geochronology, 2024)

Optimization of canopy resistance models for estimating evapotranspiration on summer maize in a semi-arid condition of China - Cun Zhan; Lu Zhao; Yaling Zhang; Xinbei Lin; Gang Zhou; Zetao Zheng (Irrigation Science, 2024)

Fine-scale monitoring of lake ice phenology by synthesizing remote sensed and climatologic features based on high-resolution satellite constellation and modeling - Jie Tong; Yaling Lin; Chenyu Fan; Kai Liu; Tan Chen; Fanxuan Zeng; Pengfei Zhan; Linghong Ke; Yongnian Gao; Chunqiao Song (Science of The Total Environment, 2024)

Synergistic enhancement of the robustness of multifunctional polyurethane via an ionic noncovalent cross-linking network and aromatic disulfides - Yaling Lin; Ning Yu; Shijie Shan; Anqiang Zhang (Chemical Engineering Journal, 2024)

Two-dimensional, high-resolution imaging of pH dynamics in the phyllosphere of submerged macrophyte using a new Nano-optode - Jianyu Lin; Yu Sun; Hao Zhang; Qiushi Shen; Li Xu; Qingfei Zeng; Yaling Su; Chao Han (Science of The Total Environment, 2023)

Preparation of micro-fibrillated cellulose fibers by a simple two-step refining process for paper- based flexible electronic devices - Chenglong Fu; Changmei Lin; Weipeng Zhang; Yaling Lin; Jinhong Xiu; Yonghao Ni; Liulian Huang (Chemical Engineering Journal, 2023)

Hepatoma-targeting and reactive oxygen species-responsive chitosan-based polymeric micelles for delivery of celastrol - Xue Zhang; Xueya Xu; Xiaoying Wang; Yajuan Lin; Yaling Zheng; Wen Xu; Jian Liu; Wei Xu (Carbohydrate Polymers, 2023)

A critical thermal transition driving spring phenology of Northern Hemisphere conifers - Jian‐Guo Huang; Yaling Zhang; Minhuang Wang; Xiaohan Yu; Annie Deslauriers; Patrick Fonti; Eryuan Liang; Harri Mäkinen; Walter Oberhuber; Cyrille B. K. Rathgeber; Roberto Tognetti; Václav Treml; et al. (Global Change Biology, 2023)
Despite growing interest in predicting plant phenological shifts, advanced spring phenology by global climate change remains debated. Evidence documenting either small or large advancement of spring phenology to rising temperature over the spatio‐temporal scales implies a potential existence of a thermal threshold in the responses of forests to global warming. We collected a unique data set of xylem cell‐wall‐thickening onset dates in 20 coniferous species covering a broad mean annual temperature (MAT) gradient (−3.05 to 22.9°C) across the Northern Hemisphere (latitudes 23°–66° N). Along the MAT gradient, we identified a threshold temperature (using segmented regression) of 4.9 ± 1.1°C, above which the response of xylem phenology to rising temperatures significantly decline. This threshold separates the Northern Hemisphere conifers into cold and warm thermal niches, with MAT and spring forcing being the primary drivers for the onset dates (estimated by linear and Bayesian mixed‐effect models), respectively. The identified thermal threshold should be integrated into the Earth‐System‐Models for a better understanding of spring phenology in response to global warming and an improved prediction of global climate‐carbon feedbacks.

Antifungal mechanisms of polymeric quaternary ammonium salts against conidia of Fusarium oxysporum f. sp. cubense, race 4 - Wei Zhang; Yaoyao Chang; Weiqiang Zhong; Anqiang Zhang; Yaling Lin (European Journal of Plant Pathology, 2023)

Carbon transfer from the submerged macrophyte Hydrilla verticillata to zooplankton: a 13C-labeled mesocosm study - Ling Su; Zongan Jin; Lichao Xie; Yali Tang; Zhengwen Liu; Ping Zhong; Yaling Su; Qiuqi Lin (Hydrobiologia, 2021)

Simvastatin Enhances Muscle Regeneration Through Autophagic Defect-Mediated Inflammation and mTOR Activation in G93ASOD1 Mice - Yafei Wang; Lin Bai; Shuai Li; Ya Wen; Qi Liu; Rui Li; Yaling Liu (Molecular Neurobiology, 2021)

Immune effect of a Newcastle disease virus DNA vaccine with IL-12 as a molecular adjuvant delivered by electroporation - Peng Xie; Yanling Li; Yaling Li; Jianpeng Liang; Bin Xiang; Qiuyan Lin; Jiaqi Jin; Chan Ding; Chenggang Xu; Tao Ren (Archives of Virology, 2020)

Clinical characteristics of 24 asymptomatic infections with COVID-19 screened among close contacts in Nanjing, China - Zhiliang Hu; Ci Song; Chuanjun Xu; Guangfu Jin; Yaling Chen; Xin Xu; Hongxia Ma; Wei Chen; Yuan Lin; Yishan Zheng; Jianming Wang; Zhibin Hu; et al. (Science China Life Sciences, 2020)

Plasma biomarkers and plaque strain predict long-term cardiovascular events in patients with acute coronary syndrome - Mingjun Xu; Xiaobo Hu; Lin Wang; Wei Zhang; Lindi Wu; Jifu Li; Yuguo Chen; Pengfei Zhang; Haijun Su; Yaling Han; Cheng Zhang; Mei Zhang; et al. (Science China Life Sciences, 2020)

Intramuscular Delivery of scAAV9-hIGF1 Prolongs Survival in the hSOD1G93A ALS Mouse Model via Upregulation of D-Amino Acid Oxidase - HuiQian Lin; HaoJie Hu; WeiSong Duan; YaLing Liu; GuoJun Tan; ZhongYao Li; YaKun Liu; BinBin Deng; XueQin Song; Wan Wang; Di Wen; Ying Wang; et al. (Molecular Neurobiology, 2018)

Targeted mutagenesis by CRISPR/Cas9 system in the model legume Medicago truncatula - Yingying Meng; Yaling Hou; Hui Wang; Ronghuan Ji; Bin Liu; Jiangqi Wen; Lifang Niu; Hao Lin (Plant Cell Reports, 2017)

A GWA study reveals genetic loci for body conformation traits in Chinese Laiwu pigs and its implications for human BMI - Lisheng Zhou; Jiuxiu Ji; Song Peng; Zhen Zhang; Shaoming Fang; Lin Li; Yaling Zhu; Lusheng Huang; Congying Chen; Junwu Ma (Mammalian Genome, 2016)

A new flavonol glycoside from the florets of Carthamus tinctorius L. - Xue Xie; Jianming Zhou; Lin Sun; Hongda Zhang; Yiwu Zhao; Yaling Song; Xuejing Wang; Fuyong Ni; Wenzhe Huang; Zhenzhong Wang; Wei Xiao (Natural Product Research, 2016)